Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer: g(f(x)) = 4x^2 - 4x - 3
Work Shown:
g(x) = x^2 - 4
g(f(x)) = ( f(x) )^2 - 4
g(f(x)) = ( 2x-1 )^2 - 4
g(f(x)) = (2x-1)(2x-1) - 4
g(f(x)) = 4x^2-2x-2x+1 - 4
g(f(x)) = 4x^2 - 4x - 3
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.